Evaluación de la sustentabilidad de la incorporación del cultivo bajo cubierta en la horticultura platense - Blandi, María Luz (2015)
In the Horticultural Platense Region, the system of outdoor cultivation is being replaced by greenhouse cultivation associated with a high-input for its higher profitability. The adoption of technologies made exclusively for its profitability, can lead to ecological and social systems less sustainable, since the cost-benefit analysis does not include such aspects. The objective was to compare the sustainability of systems produced under plastic cover (greenhouses) with production systems outdoors in European and Bolivian farmers origins. Were analyzed as case studies, 16 horticultural establishments through semi-structured interviews and field observations. Indicators were standardized and weighted built. The cultivation under greenhouse, regardless of the type of farmer, was more sustainable, in economic dimension, growing outdoors, but was less sustainable in the ecological and social dimensions, which had large critical points. Agricultural practices conducted under greenhouse were very similar, demonstrating the limited possibilities of variation when this technology package is incorporated. The outdoor production presented some critical aspects, but were less numerous and serious than in the systems under greenhouse. The use of indicators allowed to detect problems that the cost-benefit analysis would not have been detected. The results show that technological change based on cost benefit analysis may lead to less sustainable systems, as occurred with the addition of greenhouse horticulture in the region of La Plata.